The Wordsworth dictionary of Shakespeare - Boyce,Charles (Wordsworth Editions Ltd., 1996)
Containing over 3000 entries, this work provides comprehensive information on all facets of Shakespeare's life times and works. It covers every play, including its theatrical history, a scene-by-scene synopsis and a commentary, characters, Shakespeare's contemporaries and Shakespearian actors.